The effect of knowledge sharing toward employee performance with teamwork as the moderator at PT Telkom Indonesia division of regional II Jabodetabek - Putri Ananda Nadilla (Jurnal Manajemen Maranatha, 2020)
PT Telkom Indonesia is one of the best SOE companies in Indonesia. One of the efforts made by Telkom is to always become a good corporate that they have experienced and knowledgeable human resource. This research aimed to determine the effects of knowledge sharing on employee performance with teamwork as a moderator in PT Telkom Indonesia division of regional II Jabodetabek. The research method used in this research was quantitative with multiple linear regression analysis. The basic theory used in this research is the basis theory of knowledge sharing and teamwork. The population in this study was Regional II employees of PT Telkom Indonesia that have 95 respondents as the total of respondent in this research. The sampling technique type used non-probability sampling with using convenience sampling. In this research the method was using multiple linear regression analysis methods and hypothesis testing (T test, F test, and coefficient of determination) using application called SPSS 20 for windows. The research results in this study revealed that there is a positive impact and significant relationship between knowledge sharing on employee performance partially; while from simultaneously of knowledge sharing on employee performance with teamwork as a moderator also has a positive relationship and significant effect. Conclusion from this study showed that teamwork variable moderates the relationship between knowledge sharing on employee performance in Regional II PT Telkom Indonesia.